2021
DOI: 10.3389/fhumd.2021.602368
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Texting During Early Adolescence

Abstract: Research on adolescent texting has largely focused on whether the frequency of texting is associated with well-being. Whether the motives for texting is associated with well-being is not well known. We surveyed 130 young adolescents (Mage = 12.41 years) and identified user-clusters based on their motives for texting. We then examined whether the clusters were associated with phone habits that may affect health and learning (e.g., phone placement when sleeping). Participants were asked how often they texted som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…This is consistent with Jin et al who found that problematic smartphone use (PSU) is positively correlated with FoMO [15]. Similarly, a study in the USA showed that with the increased frequency of texting FoMO score of participants was also higher [18]. It seems more than plausible that SNS use had a positive correlation with FoMO, as suggested by the results obtained by Chai et al [19], and are consistent with Yang et al in which FoMO was positively correlated with connection overload [20].…”
Section: Sociological Factorssupporting
confidence: 89%
“…This is consistent with Jin et al who found that problematic smartphone use (PSU) is positively correlated with FoMO [15]. Similarly, a study in the USA showed that with the increased frequency of texting FoMO score of participants was also higher [18]. It seems more than plausible that SNS use had a positive correlation with FoMO, as suggested by the results obtained by Chai et al [19], and are consistent with Yang et al in which FoMO was positively correlated with connection overload [20].…”
Section: Sociological Factorssupporting
confidence: 89%